Implementation of K13 in the Industrial Revolution 4.0 - Zul Afdal; Sapriyanto Sapriyanto (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2021)
The research background is the implementation of the 2013 curriculum in the industrial revolution 4.0. This type of research is qualitative research. The research data collection was carried out by interview, observation and documentation. The results of this study are 1) Changes in Graduate Competency Standards (SKL) in the Industrial Revolution 4.0. 2) Changes in Content Standards, the position of competency subjects, from subjects to subjects developed from competencies, where the core competencies include competence in spiritual attitudes, social attitudes, skills and knowledge. 3) Changes to Process Standards. Change in Process Standards means a change in learning strategies. Teachers are required to design active learning that is fun, can use learning media technology and students are facilitated to observe, ask questions, process, present, conclude, and create. 4) Changes in the assessment standards for completing report cards, teachers assess the competence of student graduates including spiritual, social, skills and knowledge, in addition to assessments using numbers / scoring, and learning assessments must measure skill abilities in the form of self-reports, global assessment scales, and act of observation in each competency. The teacher must also describe / describe the results of student assessments in each competency assessment.